A Sensory Education - Harris, Anna (Sensory Studies, 2021)
A Sensory Education takes a close look at how sensory awareness is learned and taught in expert and everyday settings around the world. Anna Harris shows that our sensing is not innate or acquired, but in fact evolves through learning that is shaped by social and material relations. The chapters feature diverse sources of sensory education, including field manuals, mannequins, cookbooks and flavour charts. The examples range from medical training and forest bathing to culinary and perfumery classes. Offering a valuable guide to the uncanny and taken-for-granted ways in which adults are trained to improve their senses, this book will be of interest to disciplines including anthropology and sociology as well as food studies and sensory studies.